Web Services Testing with soapUI. - Kankanamge, Charitha (Packt Pub., 2012)
Web Services Testing with soapUI starts with an overview of SOA and web services testing, and gets your hands dirty with a sample project which makes use of open source web service engine, Apache Axis2. All demonstrations and hands-on exercises are based on this sample project. This book is a practical and comprehensive tutorial for easy and efficient web services testing to build high quality service-oriented solutions. This book directly targets software quality assurance professionals, software project managers, and software developers interested in automated or manual testing web services.